Role of molecular chaperones and TPR-domain proteins in the cytoplasmic transport of steroid receptors and their passage through the nuclear pore - Galigniana, Mario Daniel (2010)
In the absence of hormone, corticosteroid receptors such as GR (glucocorticoid receptor) and MR (mineralocorticoid receptor) are primarily located in the cytoplasm. Upon steroid-binding, they rapidly accumulate in the nucleus. Regardless of their primary location, these receptors and many other nuclear factors undergo a constant and dynamic nucleocytoplasmic shuttling. All members of the steroid receptor family are known to form large oligomeric structures with the heat-shock proteins of 90-kDa (hsp90) and 70-kDa (hsp70), the small acidic protein p23, and a tetratricopeptide repeat (TPR)-domain protein such as FK506-binding proteins (FKBPs), cyclophilins (CyPs) or the serine/threonine protein phosphatase 5 (PP5). It has always been stated that the dissociation of the chaperone heterocomplex (a process normally referred to as receptor “transformation”) is the first step that permits the nuclear import of steroid receptors. However the experimental evidence is consistent with a model where the chaperone machinery is required for the retrotransport of the receptor through the cytoplasm and also facilitates the passage through the nuclear pore. Recent evidence indicates that the hsp90-based chaperone system also interacts with structures of the nuclear pore such as importin ß and the integral nuclear pore glycoprotein Nup62 facilitating the passage of the untransformed receptor through the nuclear pore.